Brhad Srī Badrī Nārāyana māhātmya aura cārodhāma Devaprayāgo, Pancakedāra māhātmya, tathā Gangottari : bhā. ti. sahita (Mahesānandasarmā, 1913)
Glory and significance of Hindu pilgrims centre in Garhwāl, India.